Active chlorine and chlorine radicals generation by photoelectrochemical oxidation of chloride and its greater efficiency in organic compounds abatement - Fraga, Luciano Evangelista; Anderson, Marc A.; Sene, Jeosadaque J.; Zanoni, Maria Valnice Boldrin (My University, 2011)
Active chlorine has been widely used in water and wastewater treatment both as adisinfectant and an oxidizing agent. Despite the problems caused due to the production ofby-products, the use of chlorine in water disinfection process remains the primary methodof treatment to destroy pathogens and thereby is used to provide public health protection.The electrochemical oxidation of chlorides in water has long been a very successfulmethod of generating chlorine. Nevertheless, the current methods based onelectrochemical technique present some drawbacks due to the fact that they require theapplication of a high electrochemical potential for oxidizing the chloride ion and thuscompetes with oxygen evolution reaction, which elevates costs associated with thisprocess. The oxidation of chloride at lower potentials by photoelectrocatalysis of chloridehas been proposed as an alternative method, using n-type semiconductor TiO2photoanodes irradiated by UV light. The process involves the formation of chlorineradicals as intermediate, which is a source of more powerful oxidant species than activechlorine and can be successful applied to removal mutagenic/toxic organic compounds.So, the present work supplies a compact revision about photoelectrocatalytic generationof active chlorine and its radicals as intermediate and its application on organiccompounds abatement. © 2012 Nova Science Publishers, Inc. All rights reserved.